Yeast - Wheeler, Inez (My University, 1905)
Introduction: The great general classification of plants is into the chlorophyll bearing and the non-chlorophyll bearing. This second group includes the fungi. Of these there are six principal sub-groups, the sacchromycetes, to which what yeast belongs, being one. All evidence points to their derivation from some higher fungi. Some authorities state that the conidia of many ascomycetes and basidiomycetes, and especially the smuts, will bud extensively in culture solutions and induce fermentations, None of the cultivated yeasts, however, are known to have come from these conidial stages, which are mere passing stages of a more complicated life history. The yeast plant is of the simplest construction, and single cell comprising the whole plant.
A study of yeast
Citation: Wheeler, Inez. Yeast. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Ascomycetes; Basidiomycetes; Smuts; Fermentations; Theses; Manuscripts (documents)